1989
DOI: 10.1007/bf00173760
|View full text |Cite
|
Sign up to set email alerts
|

Reduced variation in the clonogenic assay obtained by standardization of the cell culture conditions prior to drug testing on human small cell lung cancer cell lines

Abstract: An advantage of established tumor cell lines compared to fresh human tumor specimens used in sensitivity assessments is the possibility of repeated experiments. Ultimately a database of sensitivity profiles on a panel of cell lines can be made and the sensitivity to new drugs compared with historical data. A prerequisite of this strategy is a minimal interexperimental variation. The sensitivity of eight human small cell lung cancer cell lines to adriamycin, daunomycin, aclacinomycin A, and mitoxantrone was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Despite a variation with a factor of two in the S-phase distribution, the interexperimental variation in LD50 is less than 25% and not correlated to the size of the S-phase. With similar S-phase variations the sensitivity with 1-h incubation varied 250% (Jensen et al, 1989 (Hill et al, 1989). Although is relatively more sensitive to DAU, the sensitivity to ADR and DAU covariate and is almost equal in most cell lines, whereas DAU is more potent than ADR with 1-h incubation.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Despite a variation with a factor of two in the S-phase distribution, the interexperimental variation in LD50 is less than 25% and not correlated to the size of the S-phase. With similar S-phase variations the sensitivity with 1-h incubation varied 250% (Jensen et al, 1989 (Hill et al, 1989). Although is relatively more sensitive to DAU, the sensitivity to ADR and DAU covariate and is almost equal in most cell lines, whereas DAU is more potent than ADR with 1-h incubation.…”
Section: Resultsmentioning
confidence: 86%
“…We have previously shown that the sensitivity of the SCCL cell lines to ADR, DAU and MITO with 1-h incubation is dependent on the size of the S-phase fraction at the time of drug exposure and that reduced variation in the clonogenic assay can be obtained by standardisation of the cell culture conditions (Jensen et al, 1989). In the present study, the inter-experimental variation after continuous incubation was evaluated on cell line NCI-N592 in three experiments with varying S-phase distribution (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of 3H-daunorubicin accumulation This was performed as described by Skovsgaard (1978) with the modification that the SCLC cells in single cell suspensions were incubated for 15 min with DNase I (0.025% w/v) (Sigma) before being exposed to daunorubicin (Versantvoort et al, 1992 (Skovsgaard, 1978 (Jensen et al, 1989a). In our attempts to rationalize 'in vitro phase II trials in SCLC' the task was therefore to obtain more dose-response curves on one batch of cells.…”
Section: Cell Linesmentioning
confidence: 99%
“…Another applicable area for the chamber is pharmacological research. Using this method, it will be possible to monitor simultaneously effects of drugs on different cell types (13) In conclusion, our novel chamber facilitates cell research, bringing an opportunity for better standardization of experimental conditions and simultaneous observation of different experimental groups, reducing the possible effect of any systematic error. A novel chamber.…”
Section: Huvec's Angiogenesis On Matrigelmentioning
confidence: 99%